The Acculturation of Kentrung â€œTri Setyo Budoyoâ€ in Dayu Village, Nglegok District, Blitar Regency: The Theoretical Study of Cultural Change (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
Kentrung â€œTri Setyo Budoyoâ€ is a traditional performing art of Blitar. That is a traditional performing art that can survive in the modern era. One of the factors affecting Kentrung â€œTri Setyo Budoyoâ€ to survive is adult acculturation on the performing arts. This article aims to (1) Describe the acculturation of art of Kentrungt â€œTri Setyo Budoyoâ€ in Dayu Village, Nglegok District, Blitar Regency. (2) Explains the innovation of Kentrung art â€œTri Setyo Budoyoâ€ in Dayu Village, Nglegok District, Blitar Regency. This research is a qualitative research, with the object of research is the art of Reog Bulkiyo in Kemloko Village, Nglegok District, Blitar Regency. Data collection techniques used through observation, interviews and documentation. Data analysis technique used is taxonomic analysis.The results showed that cultural change is universal. If there is a change in the culture of a society, it will affect other aspects such as language, knowledge system, social organization, living equipment system and technology, living livelihood system, religious system, and arts. Art Kentrung Tri Sansoso Budoyo â€œexperiencing acculturation and renewal or innovation, this happens because the culture in the community around the environment also experience acculturation. In the art that has an open mind, it will be able to get and go through these cultural changes so as to survive and thrive in the midst of changing times.